2019
DOI: 10.1016/j.enbuild.2019.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Towards metamodeling the neighborhood-level grid impact of low-carbon technologies

Abstract: Heating electrification and distributed renewable generation in the residential sector are among prominent solutions advocated for energy saving and carbon emission reduction. However, research shows these low-carbon technologies may create issues at the low-voltage (LV) distribution grid. High-level policy assessment currently lacks the support to take into account such local grid restrictions. To achieve this, we propose the use of a probabilistic simulation framework in combination with metamodeling, that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 92 publications
(167 reference statements)
0
12
0
Order By: Relevance
“…In this paper, simulation metamodeling was proposed as a technique to obtain inexpensive evaluation of garment assembly line design and determine the relationship between input variables and the response. Although metamodeling is extensively used in various engineering domains, no application for the design of complex garment assembly line system is available [19]. Consequently, the present paper demonstrates the applicability and suitability of designing a complex garment assembly line using simulation metamodeling.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In this paper, simulation metamodeling was proposed as a technique to obtain inexpensive evaluation of garment assembly line design and determine the relationship between input variables and the response. Although metamodeling is extensively used in various engineering domains, no application for the design of complex garment assembly line system is available [19]. Consequently, the present paper demonstrates the applicability and suitability of designing a complex garment assembly line using simulation metamodeling.…”
Section: Introductionmentioning
confidence: 85%
“…This is because adding the resource in the bottleneck workstation reduces both cycle time and work in progress (WIP). In spite of the fact that the metamodel was not used for further model prediction, the present study found it most suitable for inference [19] and initial solution (local optimal) for optimization process [37]. The inference was drawn from the regression metamodel to analyze the factors' effects on the production throughput.…”
Section: Regression Metamodelmentioning
confidence: 92%
See 2 more Smart Citations
“…The most commonly used approaches for metamodel construction are statistic-based and machine-learning. The former solely depends on the data received from the simulation experiments which includes linear (polynomial) regression, support vector regression, multivariate adaptive regression spline, Gaussian process regression (kriging), and radial basis function [19,[27][28][29][30][31]. The latter is based on neural networking, rule learning, and fuzzy logic [16,18,32,33].…”
Section: Introductionmentioning
confidence: 99%